A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). IV. The atrocephalum and convexior groups, and additional species of the morchella, nigrum and reflexum groups - Shavrin, Alexey V. (Zootaxa, 2020)
Two new species groups are established for East Palaearctic species of the genus Anthobium Leach, 1819: the atrocephalum group containing the widespread Palaearctic A. atrocephalum (Gyllenhal, 1827), A. formosanum Shavrin, sp. n. (Taiwan), A. hammondi Watanabe, 1990 (Japan), A. lackneri Shavrin, sp. n. (Japan: Hokkaido), and two Chinese species, A. kabateki Shavrin, sp. n. (Yunnan, Gansu) and A. marci Shavrin, sp. n. (Sichuan); the convexior group containing four new species from China: A. convexior Shavrin, sp. n. (Shaanxi, Sichuan), A. auritum Shavrin, sp. n. (Yunnan), A. kabaki Shavrin, sp. n. (Sichuan), and A. semenovi Shavrin, sp. n. (Sichuan). New species are described and illustrated. The species groups are defined, briefly discussed and a key to the species of each group is given. Additionally, a new species of the morchella group, A. inopinatum Shavrin, sp. n. (China: Yunnan) and the nigrum group, A. bengalicum Shavrin, sp. n. (India: West Bengal), are described and illustrated. New faunistic records of A. reflexum (Reitter, 1891) from Kazakhstan, Kyrgyzstan, and Tajikistan are provided.